Determinantes de acesso ao microcrédito: evidências a partir de instituição europeia - Fernandes, Andre Cesar (2022)
The present article aims to examine the determinants of granting credit using as data source the loan requests addressed to the European microfinance institution located in Belgium in the period from 2011 to 2020. To this end, data from applicant’s profile were studied, as well as the gender and experience of those responsible for evaluating the credit application. In order to verify the effect of these variables on the probability of approval of the application, statistical modeling was used as an instrument through logistic regression. The results found indicate that, in the specific case of the database used, the odds of loan approval from the institution is significantly influenced by variables related to credit history and credit score, professional situation, sector of activity, and country of birth of the client, as well as the gender of the loan officer responsible for evaluating the customer’s dossier. On the other hand, it was observed that the applicant’s gender and number of dependents do not influence the probability of credit approval.